2004
DOI: 10.1007/s00431-004-1533-7
|View full text |Cite
|
Sign up to set email alerts
|

Detection of hyperbilirubinaemia in jaundiced full-term neonates by eye or by bilirubinometer?

Abstract: The aim of this study was to compare predictions of hyperbilirubinaemia by eye, performed by trained physicians and nurses, with predictions obtained using two commercial bilirubinometers. Jaundice was assessed in 92 white and 48 non-white healthy full-term neonates using three non-invasive methods and by total serum bilirubin as the reference method. Clinical assessment of cephalocaudal progression of jaundice was carried out independently by a physician and by nurses. Simultaneously, the Minolta Airshields J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
36
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 23 publications
5
36
0
5
Order By: Relevance
“…Most previous studies on the clinical assessment of neonatal hyperbilirubinemia were conducted in the United States or Europe, were limited to a single or bi-ethnic study population and evaluated the clinical assessment of jaundice by a single observer compared to a serum bilirubin measurement taken in all the enrolled subjects (Supplementary Table 1). [5][6][7][8][9][10][11][12] Riskin et al 6 showed that neonatologists' identification of jaundice, and predicted serum bilirubin levels based on the Kramer scale, was highly correlated with serum total bilirubin levels (r ¼ 0.682, P<0.001). This study concluded: 'the clinical impression of jaundice by anyexperienced clinician is a reliable method to assess newborns for y(neonatal hyperbilirubinemia) and serum bilirubin levels are necessary only in severely jaundiced neonates.'…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Most previous studies on the clinical assessment of neonatal hyperbilirubinemia were conducted in the United States or Europe, were limited to a single or bi-ethnic study population and evaluated the clinical assessment of jaundice by a single observer compared to a serum bilirubin measurement taken in all the enrolled subjects (Supplementary Table 1). [5][6][7][8][9][10][11][12] Riskin et al 6 showed that neonatologists' identification of jaundice, and predicted serum bilirubin levels based on the Kramer scale, was highly correlated with serum total bilirubin levels (r ¼ 0.682, P<0.001). This study concluded: 'the clinical impression of jaundice by anyexperienced clinician is a reliable method to assess newborns for y(neonatal hyperbilirubinemia) and serum bilirubin levels are necessary only in severely jaundiced neonates.'…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Madlon-Kay et al 7,8 found that nurses trained in clinical assessment of jaundice adequately (r ¼ 0.61, P<0.01) identified newborns with total serum bilirubin levels <12 mg per 100 ml (205 mmol l À1 ), and all three infants with serum bilirubin levels X17 mg per 100 ml (290 mmol l À1 ) as having jaundice requiring referral to hospital. Szabo et al 9,10 reported that trained nurses and PHYs were able to identify neonates with jaundice that did not reach the abdomen or extremities in whom hyperbilirubinemia did not exceed 250 mmol l À1 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 However, visual assessment of serum bilirubin has been shown to correlate poorly with measured bilirubin levels in recent studies. 2,5,6 Blood sampling for estimation of serum bilirubin is one of the most common tests ordered in the neonatal units. The blood sampling is often done by heel prick and is painful, with potential longterm consequences.…”
mentioning
confidence: 99%